2001
DOI: 10.4049/jimmunol.167.5.2879
|View full text |Cite
|
Sign up to set email alerts
|

A Role for IL-18 in Neutrophil Activation

Abstract: IL-18 expression and functional activity has been identified in several autoimmune and infectious diseases. To clarify the potential role of IL-18 during early innate immune responses, we have explored the capacity of IL-18 to activate neutrophils. Human peripheral blood-derived neutrophils constitutively expressed IL-18R (α and β) commensurate with the capacity to rapidly respond to IL-18. IL-18 induced cytokine and chemokine release from neutrophils that was protein synthesis dependent, up-regulated CD11b ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

17
238
0
5

Year Published

2003
2003
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 273 publications
(260 citation statements)
references
References 44 publications
17
238
0
5
Order By: Relevance
“…1), in accordance with data previously shown for LPS and bacterial lipoproteins (20,42). IL-18Rs activate similar signaling pathways to TLRs, and are expressed on neutrophils (43). In keeping with this, we observed limited responses to IL-18 in our assays, but in comparison to IL-18, TLR signaling was considerably more efficacious in modulating cell surface adhesion molecule expression.…”
Section: Discussionsupporting
confidence: 79%
“…1), in accordance with data previously shown for LPS and bacterial lipoproteins (20,42). IL-18Rs activate similar signaling pathways to TLRs, and are expressed on neutrophils (43). In keeping with this, we observed limited responses to IL-18 in our assays, but in comparison to IL-18, TLR signaling was considerably more efficacious in modulating cell surface adhesion molecule expression.…”
Section: Discussionsupporting
confidence: 79%
“…12 Leung et al showed that intraperitoneal injection of IL-18 induced the accumulation of neutrophils in the peritoneal cavity. 13 Our data showed that LPS injection caused an accumulation of neutrophils in the lung associated with thickening of interstitial space and increased MPO activity in WT mice. These neutrophil-related changes were significantly inhibited in IL-18 KO mice, suggesting that the endogenous IL-18 induced accumulation of neutrophils.…”
Section: Discussionmentioning
confidence: 75%
“…IL-18 may amplify acute inflammation through promotion of neutrophil adhesion and migration, accompanied by cytokine and chemokine production, and the eventual release of granules. These effects are relevant in vivo because IL-18 administration induces peritoneal neutrophil recruitment (5). In our study, we showed that IL-18 signaling through AcPL is required to up-regulate Mac-1 expression and cytokine production by neutrophils.…”
Section: Discussionmentioning
confidence: 64%
“…Recently, it has also been demonstrated that the function of IL-18 in innate immunity can extend to neutrophil activation. IL-18 therefore may be implicated in inflammatory disorders (5).…”
mentioning
confidence: 99%